2011
DOI: 10.1093/mp/ssr019
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History of the Non-Specific Lipid Transfer Proteins

Abstract: The non-specific lipid transfer proteins (nsLTPs) are small, basic proteins characterized by a tunnel-like hydrophobic cavity, capable of transferring various lipid molecules between lipid bilayers. Most nsLTPs are synthesized with an N-terminal signal peptide that localizes the protein to the apoplastic space. The nsLTPs have only been identified in seed plants, where they are encoded by large gene families. We have initiated an analysis of the evolutionary history of the nsLTP family using genomic and EST in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
245
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(258 citation statements)
references
References 70 publications
5
245
6
2
Order By: Relevance
“…Plant lipid transfer proteins (LTPs) are so termed because, in the initial studies, the proteins were shown to transfer phospholipids and fatty acids between membranes in vitro (Kader, 1996;Boutrot et al, 2008;Edstam et al, 2011). LTPs have a low molecular mass, 6 to 10 kD, and usually a high pI, 8 to 12.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Plant lipid transfer proteins (LTPs) are so termed because, in the initial studies, the proteins were shown to transfer phospholipids and fatty acids between membranes in vitro (Kader, 1996;Boutrot et al, 2008;Edstam et al, 2011). LTPs have a low molecular mass, 6 to 10 kD, and usually a high pI, 8 to 12.…”
mentioning
confidence: 99%
“…Although LTPs were thought to function in lipid transfer between subcellular membranes, subsequent findings have shown that their nascent polypeptides possess an N-terminal endoplasmic reticulum (ER)-targeting signal peptide (Boutrot et al, 2008;Edstam et al, 2011). Thus, LTPs are likely secreted to the cell exterior for functioning.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Plant lipid transfer proteins are small basic proteins, which are able to bind hydrophobic compounds in vitro and encoded by large multigene families (Carvalho and Gomes 2007;Kader et al 2007;Edstam et al 2011). LTPs are involved in key processes in plant physiology, such as cell wall organization, stabilization of membranes, signal transduction, plant growth and development (sexual reproduction, seed development and germination) (Nielsen et al 1996;Maldonado et al 2002).…”
Section: Introductionmentioning
confidence: 99%